2018
DOI: 10.1538/expanim.17-0142
|View full text |Cite
|
Sign up to set email alerts
|

A rat model of knee osteoarthritis suitable for electroacupuncture study

Abstract: Acupuncture is widely used for knee osteoarthritis (KOA) treatment in clinical practice. In the present study, we aimed to set a standard KOA animal model for electroacupuncture (EA) study and provide an acupuncture recipe for further KOA studies. Rats intra-articularly administered monosodium iodoacetate (MIA, 0.3, 1 or 3 mg respectively, n=12 each) were evaluated for pain-like behavior: paw withdrawal mechanical threshold, weight bearing deficit, and joint pathological changes (OARSI score) until 28 days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…Notably, the reduced PWT remained longer compared with that in the decrease in the weight bearing of the ipsilateral paw (21 days vs. 7 days, respectively). In contrast to this finding, a previous study reported that MIA, at a dose of 1 or 3 mg, induced a significant reduction in the weight bearing of the ipsilateral hind limb from days 3-28 compared with control rats (14). The difference in the duration between the reduced PWT and the weight bearing may be attributed to various potential mechanisms, such as the chondrocyte degeneration, that has been observed at days 1-7 post MIA injection (24) or a potential transient inflammation that has been indicated at days 1-4 post MIA injection (25).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Notably, the reduced PWT remained longer compared with that in the decrease in the weight bearing of the ipsilateral paw (21 days vs. 7 days, respectively). In contrast to this finding, a previous study reported that MIA, at a dose of 1 or 3 mg, induced a significant reduction in the weight bearing of the ipsilateral hind limb from days 3-28 compared with control rats (14). The difference in the duration between the reduced PWT and the weight bearing may be attributed to various potential mechanisms, such as the chondrocyte degeneration, that has been observed at days 1-7 post MIA injection (24) or a potential transient inflammation that has been indicated at days 1-4 post MIA injection (25).…”
Section: Discussioncontrasting
confidence: 70%
“…For the induction of OA, the rats received intra-articular injections of MIA (1 mg in 50 µl saline) in the left knee joint. The selection of the MIA dose was based on previous studies, in which MIA exhibited significant effects in different assays (14,15). This procedure was performed under transient isoflurane (3%) inhalation anesthesia.…”
Section: Animalsmentioning
confidence: 99%
“…35 Ma et al also determined that early electroacupuncture (EA) intervention can significantly reduce joint pain and pathological lesions induced by MIA injection compared with mid-and late-term EA interventions. 36 Interestingly, a study reported that a 808 nm near infrared laser generated the antianalgesic effect from 5 to 30 min after treatment and vanished after 60 min. 37 Kim and Kim conducted a 3-week treatment using an 850 nm galliumaluminum-arsenide laser, resulting in the weight-bearing difference, PWMT, and PWL significantly reversed, and the serum levels of TNF-a, IL-1b, and IL-6 also decreased in a MIA-induced KOA model.…”
Section: Effects Of Laser Moxibustion On Mia-induced Koamentioning
confidence: 99%
“…The rats in group M were subjected to KOA establishment without any subsequent treatment, simulating the natural recovery of KOA without any treatment. For the MS group, according to Ma et al [ 13 ], the location of the treatment site is shown in Figure 1 , where Dubi (ST35) is located in the depression outside the patellar ligament and Zusanli (ST36) is located at about 5 mm inferior of the capitulum fibulae and posterior-lateral to the hind-limb knee joint [ 14 ]. After KOA was established in the rats, the lit moxibustion strip (diameter 7 mm, length 12 cm) was placed 1-2 cm away from the treatment acupoint, the skin temperature “of” the acupoint was maintained at 43 ± 1°C, and the treatment lasted for 30 min [ 10 ].…”
Section: Methodsmentioning
confidence: 99%